2019
DOI: 10.1177/1474704919834502
|View full text |Cite
|
Sign up to set email alerts
|

(Pretty) Lady First: Effects of Mate-Related Motives on the Item-Selection Orders of Faces With Varying Attractiveness

Abstract: Evolutionary theories suggest that fundamental mating-related motives might exert specific effects on human cognition and behaviors. Based on the evolutionary perspective, our prior research illustrated that the activation of mating-related motives leads to a study-time allocation bias toward highly attractive female faces. While study-time allocation is one of the aspects of the self-regulated learning process, it is unclear whether mating motives affect study decision behaviors (as measured by item-selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…As a result, the mediating effects diminished. As previous evolutionary psychology research has focused on the fundamental motive effects on cognitive processes (e.g., attention and metacognition; Maner et al, 2007;Zhang et al, 20 ), the findings of our study expand the explanatory scope of evolutionary theory by revealing the mediating effects of popularity goals on the relationship between social cognition factors and social behaviors (active defending behaviors). Our findings are not consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…As a result, the mediating effects diminished. As previous evolutionary psychology research has focused on the fundamental motive effects on cognitive processes (e.g., attention and metacognition; Maner et al, 2007;Zhang et al, 20 ), the findings of our study expand the explanatory scope of evolutionary theory by revealing the mediating effects of popularity goals on the relationship between social cognition factors and social behaviors (active defending behaviors). Our findings are not consistent with those of previous studies.…”
Section: Discussionsupporting
confidence: 62%
“…Evolutionary psychology claims that individuals develop domain-specific cognition or behavioral outcomes to attain their goals (Kenrick et al, 2010;Zhang et al, 20 ). According to resource control theory, popularity is an important social resource in individuals' social life; individuals adopt prosocial (e.g., stopping the bullies, comforting the victim) or coercive (e.g., 20 20 aggressive, bullying, or delinquency) behavioral strategies to achieve their social goals (to access or protect their popularity in peer groups; Hartl et al, 2020;Hawley, 1999;Hawley, 2014;Kiefer & Wang, 2016;Ranney & Troop-Gordon, 2020).…”
Section: Mediating Role Of Popularity Goalsmentioning
confidence: 99%
“…Identification of potential rivals could facilitate the use of mate-guarding tactics (Maner, Gailliot, & DeWall, 2007). Indeed, previous studies found that women pay more attention to attractive rivals when mate-guarding was activated (W. Li et al, 2015;Y. Zhang et al, 2019).…”
Section: Mate-guarding and Attentiveness To Attractive Rivalsmentioning
confidence: 99%
“…Indeed, previous studies found that women pay more attention to attractive rivals when mate-guarding was activated (W. Li et al, 2015; Y. Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 98%